2004
DOI: 10.1002/dvdy.20075
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and expression of D2 and D3 dopamine receptor genes in zebrafish

Abstract: We mined the zebrafish genomic sequence database and identified contigs containing segments of several dopamine receptor genes. By using a polymerase chain reaction amplification strategy, we generated full-length cDNAs encoding a single dopamine D3 receptor and three distinct D2 receptor subtypes. Zebrafish dopamine receptor genes were mapped by using the T51 radiation hybrid panel. The D3 receptor gene (drd3) mapped to linkage group (LG) 24. The three D2 receptor genes were localized to LG 15 (drd2a), LG 16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
122
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 46 publications
12
122
1
2
Order By: Relevance
“…Topographically, the patterns of drd1 expression are similar to the expression of dopamine transporters (Holzschuh et al, 2001), tyrosine hydroxylase (Guo et al, 1999(Guo et al, , 2000Holzschuh et al, 2001;Gao et al, 2005), and dopamine D2 receptors (Boehmler et al, 2004). However, the onset time of drd1 expression appeared to be delayed several hours compared with the expression of other dopaminergic system-specific genes.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Topographically, the patterns of drd1 expression are similar to the expression of dopamine transporters (Holzschuh et al, 2001), tyrosine hydroxylase (Guo et al, 1999(Guo et al, , 2000Holzschuh et al, 2001;Gao et al, 2005), and dopamine D2 receptors (Boehmler et al, 2004). However, the onset time of drd1 expression appeared to be delayed several hours compared with the expression of other dopaminergic system-specific genes.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, the zebrafish (Danio rerio) has emerged as a model vertebrate for molecular and genetic studies of the dopaminergic system (Guo et al, 1999(Guo et al, , 2000Holzschuh et al, 2001;Ma and Lopez, 2003;Boehmler et al, 2004;Gao et al, 2005). By screening the F3 generation of chemically mutagenized zebrafish, for example, Guo et al (1999Guo et al ( , 2000 isolated a large number of gene mutations that disrupt the development or function of the dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several components of the DA biosynthetic and signaling pathways are expressed in the zebrafish larval brain (Holzschuh et al, 2001;Boehmler et al, 2004Boehmler et al, , 2007McLean and Fetcho, 2004;Anichtchik et al, 2006;Li et al, 2007), but which intracellular pathways are modulated by DA and its role in mediating behavior, as well as how DA signaling regulates zebrafish brain development, is not well characterized. Previous studies have demonstrated that DA is involved in larval motor regulation and that this is mediated, in part, by cAMP signaling (Boehmler et al, 2007;Thirumalai and Cline, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Orthologous DA D 1 -like and D 2 -like receptor expression is detected in specific embryonic and early larval brain regions (Boehmler et al, 2004(Boehmler et al, , 2007Li et al, 2007). Furthermore, behavioral studies indicate that the neural cells are competent to respond to DA signaling at a time when simple motor behaviors are emerging in the young larvae (Boehmler et al, 2007;Bretaud et al, 2007;Thirumalai and Cline, 2008).…”
Section: Introductionmentioning
confidence: 99%